Uji toksisitas menggunakan metode BSLT dan uji antibakteri Staphylococcus aureus dan Escherichia coli ekstrak dan fraksi batang karamunting (Rhodomyrtus tomentosa (Aiton) Hassk.) - Siregar , Anisah; Ridwanto, Ridwanto; Daulay , Anny Sartika; Nasution , Haris Munandar (Journal of Pharmaceutical and Sciences, 2025)
Natural ingredients have been widely used in medicine, commonly referred to as "back to nature," meaning "kembali ke alam." Herbal medicine is recognized as one of the most practical and effective treatment modalities available. One medicinal plant is the stem of Rhodomyrtus tomentosa (Aiton) Hassk., which belongs to the Myrtaceae family and has the potential as an antibacterial remedy. To ensure traditional medicine fulfills its responsibility, scientific research, such as toxicity testing, is necessary. The Brine Shrimp Lethality Test (BSLT) is a preliminary test to assess the toxic effects of plants. This study aims to determine the secondary metabolite compounds, toxicity levels, and antibacterial activity of ethanol extract and n-hexane and ethyl acetate fractions of Rhodomyrtus tomentosa stem. The study includes characterization, phytochemical screening, and toxicity testing by observing the mortality rate of Artemia salina Leach larvae, expressed as LC50. Antibacterial testing against Staphylococcus aureus and Escherichia coli was conducted using the disc diffusion method. The results of phytochemical screening of simplicia powder, ethanol extract, and n-hexane and ethyl acetate fractions of Rhodomyrtus tomentosa stem tested positive for alkaloids and triterpenoids/steroids. Simplicia powder, ethanol extract, and the ethyl acetate fraction also contained secondary metabolites such as flavonoids, tannins, and saponins. The toxicity test results using probit analysis showed that the LC50 value of the extract was 97.6787 µg/mL, the LC50 value of the ethyl acetate fraction was 71.4331 µg/mL, and the LC50 value of the n-hexane fraction was 57.4910 µg/mL. Therefore, it can be concluded that the extract and the n-hexane and ethyl acetate fractions of Rhodomyrtus tomentosa stem are toxic. The antibacterial test results showed that the extract and the n-hexane and ethyl acetate fractions exhibited inhibitory activity against Staphylococcus aureus and Escherichia coli.